The Contemporary Russian Patriotic Song as a Phenomenon of a Post-Traumatic Society’s Condition - Lassan, Eleonora (Slavistica Vilnensis, 2022)
The author has addressed both Soviet and post-Soviet song discourse a number of times already, as it is in the song discourse that one can discern the reflection of the ideological attitudes on the one hand and a certain indicator of how the spirit of the times changes on the other. The 2000s increased the impact channels of the song genre by adding the visual channel to the ones already existing; that is, a truly popular song is disseminated in clips. There appeared a new kind of a “civil” song in the Russian song space. It explicitly coincides with the propagandist trends, either the ones being created or the ones that have already been set. This song discourse is full of ressentiment motives that have rallied the present-day Russian authorities and a certain part of the population. Their aggressively advancing potential is related to the traumatic condition of the society experiencing a particular shock caused by the feeling of the loss of the erstwhile grandeur of the country. The author deals with the functions of such a propagandistic song that can be characterized as an additional propagandistic narrative on the examples of Gazmanov’s and Bichevskaya’s songs.